Membangun Keterampilan SDM melalui Program Pengabdian untuk Menghadapi Era Digital di UMKM Kecamatan Meureubo Aceh Barat - Mukhsinuddin, Mukhsinuddin; Efendi, Sumardi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2025)
Digital transformation presents a major challenge for MSME actors in Meureubo Subdistrict, Aceh Barat, where most businesses still rely on conventional methods. This community service program aimed to enhance digital literacy and online marketing skills, helping MSMEs become more adaptable and competitive in the digital era. The program adopted a community-based service and participatory training approach, involving 30 MSME owners from the culinary, handicraft, and service sectors. Activities included a four-day intensive training covering digital marketing (Facebook, Instagram, WhatsApp Business), e-commerce fundamentals (Shopee, Tokopedia), and digital financial management, delivered through group discussions, simulations, and hands-on practice. This was followed by one month of mentoring to support practical application in each participant’s business. Data were collected through questionnaires (pre- and post-test), participatory observation, and semi-structured interviews, and analyzed using descriptive statistics and thematic coding. The results showed significant improvements: ownership of marketplace accounts increased by 59% (from 28% to 87%), use of business social media rose by 55% (from 35% to 90%), and participants’ confidence in managing digital accounts grew by 45% (from 25% to 70%). In-depth interviews also revealed an average revenue increase of 10–20% within two weeks after training, driven by more targeted digital promotions and the confidence to try live streaming features. Beyond technical skills, the program fostered a culture of collaboration and a shared awareness of the importance of digitalization. This participatory, practice-based training model proved effective in supporting MSME digital transformation and can be replicated in other areas with similar contexts.